Understanding co-production of injury research in Australian Aboriginal and Torres Strait Islander communities: a comprehensive scoping review - Genevieve Westacott; Victoria McCreanor; Susanna Cramb; Silvia Manzanero; Kim Vuong; Michelle Allen; Shannon Dias; Geoffrey Binge; Arpita Das (Injury Epidemiology)
Abstract Background Injury causes significant burden on Australian Aboriginal and Torres Strait Islander communities. However, a considerable portion of the research conducted in this area has been carried out by Western researchers. It has been acknowledged that historical research methodologies and discourses around Aboriginal and Torres Strait Islander research may not be suitable or beneficial. Co-production methodologies offer opportunities for research to be developed collaboratively ensuring meaningfulness of results and appropriate protection for participants. A scoping review was undertaken to investigate the use of co-production methodologies in research within the unintentional injuries space for Australian Aboriginal and Torres Strait Islander communities over time. Main body A systematic search was conducted using PubMed, ProQuest, Embase and Indigenous Health Infonet databases. Study characteristics, remoteness, injury topic, co-production methods and elements were extracted from eligible studies. The search revealed 4175 papers, from which 39 studies were included in this scoping review. It was found that 69% of studies were fully co-produced with community. Studies predominately focused on general injury, falls prevention or brain injury rehabilitation. The most heavily utilised co-production strategy was the inclusion of Aboriginal and Torres Strait Islander researchers into the writing and research team. This helped the collection of culturally safe data and appropriate interpretation of results. Conclusion There is growing diversity among co-production methodologies, better enabling meaningful engagement between community and research. This co-production helps decolonise the research process to privilege Aboriginal voices, however, more work is needed to appropriately capture Indigenous perspectives.